2019
DOI: 10.1111/cpr.12698
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNAs in cutaneous biology and proliferative skin diseases: Advances and perspectives

Abstract: Advances in transcriptome sequencing have revealed that the genome fraction largely encodes for thousands of non‐coding RNAs. Long non‐coding RNAs (lncRNAs), which are a class of non–protein‐coding RNAs longer than approximately 200 nucleotides in length, are emerging as key epigenetic regulators of gene expression recently. Intensive studies have characterized their crucial roles in cutaneous biology and diseases. In this review, we address the promotive or suppressive effects of lncRNAs on cutaneous physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 117 publications
3
26
0
Order By: Relevance
“…Two major classes of non-coding RNA play a role in the pathogenesis of psoriasis: long non-coding RNA (lncRNA) and microRNA (miRNA) [32][33][34][35][36].…”
Section: Non-coding Rnamentioning
confidence: 99%
“…Two major classes of non-coding RNA play a role in the pathogenesis of psoriasis: long non-coding RNA (lncRNA) and microRNA (miRNA) [32][33][34][35][36].…”
Section: Non-coding Rnamentioning
confidence: 99%
“…They also identified distinct tissue-specific expression patterns and epigenetic profiles for novel lncRNAs. Altogether, these results indicate that great deals of lncRNAs are involved in the immune pathogenesis of psoriasis [ 87 , 91 ].…”
Section: Long Non-coding Rna In Psoriasismentioning
confidence: 99%
“…lncRNA are involved in epigenetic silencing, splicing process regulation, translation control, regulating the apoptosis and cell cycle control. Moreover, the expression levels of various lncRNA are closely related to epidermal differentiation and immunoregulation [85][86][87][88][89][90][91][92][93]. There are many examples illustrating that ln-cRNAs are also involved in regulation of a variety of skin pathological conditions including skin cancer, wound healing and psoriasis [85][86][87][88].…”
Section: Long Non-coding Rna In Psoriasismentioning
confidence: 99%
“…The transcript of maternally expressed gene 3 ( MEG3 ) is an lncRNA that does not encode for protein and has regulatory effect on cell function (Zhang , 2018 ; Tang et al 2020 ; Chanda 2018 ). Recent studies have shown that the abnormal expression of MEG3 in placental villi is closely associated with the preeclampsia and MEG3 can regulate the proliferative and invasive capacities of trophoblasts (Zhang 2015 ; Yu 2018 ).…”
Section: Introductionmentioning
confidence: 99%